2007
DOI: 10.1681/asn.2007020140
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cells Protect against Acute Tubular Injury via an Endocrine Effect

Abstract: Emerging evidence suggests that the intravenous injection of bone marrow-derived stromal cells (BMSC) improves renal function after acute tubular injury, but the mechanism of this effect is controversial. In this article, we confirm that intravenous infusion of male BMSC reduced the severity of cisplatin-induced acute renal failure in adult female mice. This effect was also seen when BMSC (or adipocyte-derived stromal cells (AdSC)), were given by intraperitoneal injection. Infusion of BMSC enhanced tubular cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
457
4
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(488 citation statements)
references
References 41 publications
(47 reference statements)
19
457
4
8
Order By: Relevance
“…31 These authors suggested that homing is not an absolute requirement for the beneficial effect of MSC-based therapy, as the intraperitoneal administration of MSC-conditioned medium to mice with cisplatin-induced AKI is sufficient to diminish tubular cell apoptosis, to increase tubular cell survival and to limit renal injury. 31 These data indicate that factors secreted by MSCs are responsible for their renoprotective effect, suggesting an endocrine action. However, the nature of the factors responsible for the beneficial paracrine effects of MSCs remains elusive.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…31 These authors suggested that homing is not an absolute requirement for the beneficial effect of MSC-based therapy, as the intraperitoneal administration of MSC-conditioned medium to mice with cisplatin-induced AKI is sufficient to diminish tubular cell apoptosis, to increase tubular cell survival and to limit renal injury. 31 These data indicate that factors secreted by MSCs are responsible for their renoprotective effect, suggesting an endocrine action. However, the nature of the factors responsible for the beneficial paracrine effects of MSCs remains elusive.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Therefore, it has been proposed that MSCs must provide paracrine and/or endocrine factors that explain their positive effects on kidney injury [41]. Evidence for this paracrine/endocrine process was provided by Bi et al [42], using a model of cisplatin-induced renal damage. This study showed that the apparent reparative function of MSCs could be achieved via an intraperitoneal injection of the MSC-conditioned medium alone.…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%
“…MSCs have been shown to secrete a number of growth factors [41]. Imberti et al [43] suggest that this humoral function results from IGF1, whereas Bi et al [42] attributed it to a combination of HGF, IGF1 and EGF. A recent paper by Togel et al [44] suggests that VEGF is the critical factor in the renoprotection afforded by MSCs.…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%
“…The systemic delivery of BM-MSCs after a variety of acute renal injuries (glycerol, mercury chloride, cisplatin, and ischemic injury) elicits a reparative effect in animal models. [8][9][10][11][12][13] Although it was initially thought to occur by the transdifferentiation of MSCs into renal epithelium, 8 the observed improvements in histology and function are now considered to result from the secretion of proreparative factors. 9,12,14,15 Cells with MSC-like properties have now been isolated from many solid organs.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] Although it was initially thought to occur by the transdifferentiation of MSCs into renal epithelium, 8 the observed improvements in histology and function are now considered to result from the secretion of proreparative factors. 9,12,14,15 Cells with MSC-like properties have now been isolated from many solid organs. 16 These tissue-derived MSC-like cells apparently represent perivascular cells on the basis of marker expression (CD146 + NG2 + CD140b + ) [16][17][18] and have been proposed to support local tissue turnover and/or repair.…”
mentioning
confidence: 99%